2011
DOI: 10.4067/s0716-97602011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and redox-protective activities of citronellal

Abstract: The anti-infl ammatory and redox protective effects of the citronellal (CT) were evaluated using in vivo and in vitro tests. Intraperitoneal (i.p.) administration of CT (50, 100, and 200 mg/kg) inhibited (p < 0.05) the carrageenan-induced leukocyte migration to the peritoneal cavity. Additionally, the carrageenan-and arachidonic acid-induced rat hind paw edema was signifi cantly inhibited (p < 0.05) by i.p. administration of 100 and 200 mg/kg of the compound. When the redox activity was evaluated, CT (200 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Previous studies have already demonstrated the benefits of monoterpenes in the treatment of various signs and symptoms, from those of acute manifestations, to those of chronic manifestation, pointing to this class of natural products as an alternative for the development of new drugs (Guimarães et al, 2014(Guimarães et al, , 2013Melo et al, 2011;Seol et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already demonstrated the benefits of monoterpenes in the treatment of various signs and symptoms, from those of acute manifestations, to those of chronic manifestation, pointing to this class of natural products as an alternative for the development of new drugs (Guimarães et al, 2014(Guimarães et al, , 2013Melo et al, 2011;Seol et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antimicrobial activity some monoterpenes, such as citronellal, has anti-inflammatory (Melo et al, 2011b), antinoceptive Quintans-Junior et al, 2010), larvicidal (Barros et al, 2009) and anticancer activities (Osato, 1965;Osato et al, 1961;Osato et al, 1954), while p-cymene modulates cytokine production (Zhong et al, 2012) has anti-inflammatory (Xie et al, 2012) and antinocceptive activity (Bonjardim et al, 2012). Now, we demonstrate, through this work, that citronellal, p-cymene and carvacrol have relaxing effect on guinea-pig trachea and carvacrol has greater efficacy and potency among the three monoterpenes tested.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also one of the compounds responsible for the aroma of Cymbopogon, a plant known for its ability to repel insects. Citronellal also displays larvicidal, anti-inflammatory, antinociceptive, antioxidant [18,19], antimicrobial [20], and bronchodilator effects [4].…”
Section: Gc-ms Analysis Of the Chemical Constituents Present In Essenmentioning
confidence: 99%